1999
DOI: 10.1523/jneurosci.19-12-04695.1999
|View full text |Cite
|
Sign up to set email alerts
|

A Furosemide-Sensitive K+–ClCotransporter Counteracts Intracellular ClAccumulation and Depletion in Cultured Rat Midbrain Neurons

Abstract: Efficacy of postsynaptic inhibition through GABA A receptors in the mammalian brain depends on the maintenance of a Cl Ϫ gradient for hyperpolarizing Cl Ϫ currents. We have taken advantage of the reduced complexity under which Cl Ϫ regulation can be investigated in cultured neurons as opposed to neurons in other in vitro preparations of the mammalian brain. GABA is the main inhibitory transmitter in the mammalian brain. The dominant effect of GABA A receptor activation is a hyperpolarization caused by C l Ϫ fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
146
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 41 publications
14
146
1
Order By: Relevance
“…Furosemide, when tested on 3 control neurons (in which no theta-bursts were given) did not significantly changed the RP of the IPSC (before furosemide application: 63.17 ± 0.59 mV & after furosemide application: 61.92 ± 0.46 mV; P > 0.05). This observation is consistent with those of (Banks et al, 1998;Jarolimek et al, 1996;Jarolimek et al, 1999;Ouardouz and Sastry, 2005;Pearce, 1993).…”
Section: Nih Public Accesssupporting
confidence: 92%
See 1 more Smart Citation
“…Furosemide, when tested on 3 control neurons (in which no theta-bursts were given) did not significantly changed the RP of the IPSC (before furosemide application: 63.17 ± 0.59 mV & after furosemide application: 61.92 ± 0.46 mV; P > 0.05). This observation is consistent with those of (Banks et al, 1998;Jarolimek et al, 1996;Jarolimek et al, 1999;Ouardouz and Sastry, 2005;Pearce, 1993).…”
Section: Nih Public Accesssupporting
confidence: 92%
“…Furosemide, when tested on 3 control neurons (in which no theta-bursts were given) did not significantly changed the RP of the IPSC (before furosemide application: 63.17 ± 0.59 mV & after furosemide application: 61.92 ± 0.46 mV; P > 0.05). This observation is consistent with those of (Banks et al, 1998;Jarolimek et al, 1996;Jarolimek et al, 1999;Ouardouz and Sastry, 2005;Pearce, 1993).Previous studies in our laboratory indicated that tetanic stimulations of inputs induce a shift in the RP for GABA-ergic PSCs of neonatal rat DCN neurons (Ouardouz and Sastry ., 2000;Ouardouz and Sastry., 2005) and neonatal rat hippocampal CA1 pyramidal neurons (Ouardouz et al, 2006). In DCN neurons, the tetanus-induced negative shift in the RP seems to be due to an increased expression and activation of KCC-2 through an activation of protein kinase A, protein synthesis and activation of protein phosphatases (Ouardouz and Sastry, 2005).…”
supporting
confidence: 90%
“…Elsewhere in the adult CNS, GABA A and GABA C receptor activation can evoke both depolarizing and hyperpolarizing postsynaptic potentials from the same neuron (31). Moreover, different compartments of a single neuron have been reported to contain different intracellular chloride concentrations (32,33) in a manner that is consistent with the differential distribution of the Na-K-Cl and K-Cl cotransporters in the membranes of the proximal and distal portions of the dendrites, respectively. In addition, SAC dendrites exhibit a differential distribution of synaptic proteins because synaptic specializations are present on the distal, and not proximal, portions of their dendrites (20,27,28).…”
Section: Discussionmentioning
confidence: 77%
“…Finally, the results suggest that subcellular specializations, such as the differential distribution of the Na-K-Cl and K-Cl cotransporters, can mediate the neural computation of complex information. As occurs in the retina, it is likely that the differential distribution of the Na-K-Cl and K-Cl cotransporters may also mediate neural computations elsewhere in the brain, such as in the midbrain and hippocampus, where the processes of individual neurons exhibit a chloride gradient (32,33). Indeed, the asymmetric release of GABA from interneurons in the brain at dendrodendritic synapses may be an important means by which the brain processes information.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, control measurements of somatic E GABA yielded a value of Ϫ40.7 Ϯ 0.41 mV (n ϭ 26), demonstrating that the somatic [Cl Ϫ ] i of CA1 pyramidal neurons was clamped at the [Cl Ϫ ] of the pipette. Thus, under these conditions, a negative deviation of the dendritic E GABA from the somatic value (i.e., ⌬E GABA ) is a quantitative measure of the efficacy of Cl Ϫ extrusion (Jarolimek et al, 1999;Khirug et al, 2005). Somatic and dendritic E GABA values were determined from the current-voltage rela-tions, obtained by sequentially clamping the membrane potential at different holding potentials with a 5 mV increment and a 10 s step interval.…”
Section: Methodsmentioning
confidence: 99%